Comparison Between Placenta Accreta Index and Tovbin Score as A Predictor of Placenta Accreta Spectrum Disorders (PASD) - Willy Angga Dinata; Alini Hafiz; Arufiadi Anityo Mochtar; Julian Dewantiningrum; Putri Sekar Wiyati; Ratnasari Dwi Cahyanti (RSUP Dr. Kariadi, 2024)
Background : The incidence of Placenta Accreta Spectrum Disorders (PASD) in developed countries has reportedly increased 10-fold in the last 50 years. The significant increase was followed by an increase in the number of caesarean section from 12.5% to 23.5% in the last 10 years. Maternal morbidity related to PASD events reaches 7% in intraoperative and postoperative actions, while the morbidity reaches 60%. In cases of late diagnosis, maternal mortality with placenta accreta reaches 30%. Efforts to prevent maternal morbidity and mortality can be carried out by early detection at antenatal care visits. The Placenta Accreta Index (PAI) and Tovbin scoring systems based on the results of ultrasound examination can be used to screening for placenta accreta. Objective: To analyze the comparison of the accuracy of the PAI and Tovbin scoring systems in predicting the incidence of Placenta Accreta Spectrum Disorder (PASD). Method: The study used an analytic observational with a cross sectional design. Sampling was done by consecutive sampling method. There were 35 subjects who met the inclusion and exclusion criteria. PAI and Tovbin scoring were performed on each selected subject. The accuracy of the PAI and Tovbin scoring systems was confirmed by establishing a diagnosis based on PASD histopathology. Results: The PAI scoring system in predicting PASD has a sensitivity value of 79.31%, a specificity of 83.33%, a positive predictive value (NDP) of 95.83%, a negative predictive value (NDN) of 45.45%, an accuracy of 80.00%. While the Tovbin scoring system obtained a sensitivity value of 86.21%, specificity of 83.33%, NDP of 96.15%, NDN of 55.56%, accuracy of 85.71 %. Conclusion: In the comparison of scoring systems, it was found that the Tovbin scoring system has almost the same sensitivity and accuracy and the same specificity in predicting Placenta Accreta Spectrum Disorder (PASD).